2021
DOI: 10.1002/lt.26383
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Prophylaxis of Gastric Variceal Bleeding: A Systematic Review and Network Meta‐Analysis

Abstract: There is no clear consensus regarding the optimal approach for secondary prophylaxis of gastric variceal bleeding (GVB) in patients with cirrhosis. We conducted a systematic review and network meta-analysis (NMA) to compare the efficacy of available treatments. A comprehensive search of several databases from each database's inception to March 23, 2021, was conducted to identify relevant randomized controlled trials (RCTs). Outcomes of interest were rebleeding and mortality. Results were expressed as relative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 51 publications
0
12
0
1
Order By: Relevance
“…Moreover, NSBB therapy alone did not demonstrate a benefit in terms of preventing gastric variceal rebleeding compared with most interventions, nor reduce mortality compared with endoscopic injection of cyanoacrylate alone (RR 4.12, 95 %CI 1.50 to 11.36) and endoscopic injection of cyanoacrylate plus NSBB (RR 5.61, 95 %CI 1.91 to 16.43). This study suggested that BRTO may be the best intervention in preventing gastric variceal rebleeding (secondary prophylaxis), whereas an NSBB given as monotherapy cannot be recommended; however, head-to-head direct comparator studies are much needed 132 .…”
Section: Post-endoscopy Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, NSBB therapy alone did not demonstrate a benefit in terms of preventing gastric variceal rebleeding compared with most interventions, nor reduce mortality compared with endoscopic injection of cyanoacrylate alone (RR 4.12, 95 %CI 1.50 to 11.36) and endoscopic injection of cyanoacrylate plus NSBB (RR 5.61, 95 %CI 1.91 to 16.43). This study suggested that BRTO may be the best intervention in preventing gastric variceal rebleeding (secondary prophylaxis), whereas an NSBB given as monotherapy cannot be recommended; however, head-to-head direct comparator studies are much needed 132 .…”
Section: Post-endoscopy Managementmentioning
confidence: 99%
“…In addition, a recently published network meta-analysis (nine RCTs with 647 patients who had a history of GVH and follow-up of more than 6 weeks) compared the efficacy of available secondary prophylaxis treatments [132]. BRTO was associated with a lower risk of rebleeding when compared with NSBB therapy alone (RR 0.04, 95 %CI 0.01 to 0.26) and endoscopic injection of cyanoacrylate alone (RR 0.18, 95 %CI 0.04 to 0.77).…”
Section: Secondary Prophylaxis: Prevention Of Recurrent Esophageal Or...mentioning
confidence: 99%
“…Втручання включали призначення НСББ, БРТО, ЕІЦ, ендоскопічне лігування варикозних вен, ендоскопічну склеротерапію під контролем EУСГ-ЕІЦ, ТВПШ. БРТО виявилася найкращим заходом для запобігання повторній кровотечі, тоді як монотерапія β-блокаторами -найгіршим [49].…”
Section: вторинна профілактика кровотечі зі шлункових вариксівunclassified
“…Advances in endoscopic treatment have enabled the safe and effective treatment of esophageal varices. By contrast, gastric varices (GV) are often technically difficult to treat endoscopically, and additional or alternative treatments are required to achieve complete hemostasis of bleeding from GV [[2]–[4]].…”
Section: Introductionmentioning
confidence: 99%